(untitled) (Economic and Political Thought, 2017)
The objective of the present paper is to discuss Ukraine’s position in both the European Neighbourhood Policy (established in 2004) and the Eastern Partnership project based on the policy. The Orange Revolution of 2004 and events of 2013/2014 in Ukraine labeled the Euromaidan indicated that the European direction of the country is of critical importance for a considerable part of Ukrainian society and political elites. Integration with the EU presents a necessity for a civilizational choice for Ukraine. The fact that, of all states located on the EU’s eastern border, it is Ukraine which poses the greatest challenge, is noteworthy. Ukraine’s geopolitical and geoeconomic position make it a key player both for the EU and Russia as well.